EFEKTIFITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATERI TEKS PROSEDUR PADA MATA PELAJARAN BAHASA INDONESIA - Setiawan, Sartika (JGuruku: Jurnal Penelitian Guru, 2023)
THE EFFECTIVENESS OF PROBLEM BASED LEARNING (PBL) LEARNING MODELS TO IMPROVE LEARNING OUTCOMES OF PROCEDURE TEXT MATERIALS IN INDONESIAN LANGUAGE SUBJECTS ABSTRACT From the results of teaching experience and observation results at SDN 4 Nasol, the educational process still uses conventional learning models, so that student activity in the learning process is low, this has an impact on decreasing student learning outcomes. Based on this case, a model was developed using the Problem Based Learning learning model which aims to determine the Application of the Project Based Learning Learning Model to Improve Student Activities and Learning Outcomes in Class 5 Procedure Text Material for Indonesian Language Subjects at SDN 4 Nasol, Cikoneng, Ciamis which results from several studies can increase competence. This type of research is Classroom Action Research which uses two cycles with the research subjects being 5th grade students at SDN 4 Nasol, Cikoneng District, Ciamis Regency. Ciamis consists of 22 students. The data collection method uses lecture, question and answer, discussion and independent assignment methods. From the analysis of research data, it is known that in cycle I the average value of student learning outcomes was 60%, increasing to 91% in cycle II. The application of the Problem Based Learning Model can also increase student learning activity where in cycle I student activity was 60% increasing to 91% in cycle II. Keywords: learning model, Problem Based Learning, learning activities, learning outcomes.